Clinical Features of Early Diagnosis and a Choice of Method of Surgery for Hirschsprung Disease in Infants - Ulugbek A. Khamroev1, Bakhtiyor B. Ergashev2, Rajabboy I. Isroilov3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this study is to improve the results of surgical treatment of Hirschsprung’s disease in infants bychoosing the most effective method.This article presents the results of the treatment of Hirschsprung’s disease in 61 patients of infancy. However,immediate and long-term results of the children’s treatment with HD, operated on in infancy, using thetraditional Soave-Boley method and modern minimally invasive technologies according to TENTC andthe Georgeson method, which show different results, have been studied. Among 26 patients who had beenoperated on by the Soave - Boley method, the following results were obtained : excellent - in 10 (38.4%);good - in 8 (30.7%); satisfactory - in 6 (23%) and unsatisfactory - in 2 (7.6%). Among 29 patients operatedon by the TEPT method, except for one patient, excellent and good results were obtained in 28 (96.6%)patients. What is more, among 6 patients who had been operated on by the Georgeson method, excellentand good results were obtained in all cases; there were no satisfactory or unsatisfactory results. It shouldbe noted that among the operated HD patients according to the Soave-Boley method, there were severepatients, of which 7 patients had a colostomy in the neonatal period.At the same time, radical one-stage surgical treatment for distal forms of HD using minimally invasive TEPTmethod is a priority in infancy, which can reduce complications to a minimum with improved functionaloutcomes of treatment, relative to two-stage treatment.